Analisis Proses Pembelajaran Daring pada Mata Pelajaran IPA Materi Energi dan Perubahannya melalui Pendekatan Saintifik Kelas IV di MI Miftahul Ulum Bago Pasirian - Warda Maghfiroh (Jurnal Riset Madrasah Ibtidaiyah, 2022)
The Coronavirus Disease (Covid-19) virus is increasingly rampant and has caused several sectors to close including the education sector. Spontaneously, Indonesia issued a policy to implement online learning from home so that the educational process continues even though schools are closed. The use of online learning media is an alternative choice so that learning activities can continue. This study aims to analyze the online learning process in the science subject matter of Energy and its Changes through a scientific approach at the fourth grade level at MI Miftahul Ulum Bago Pasirian. With the current situation and conditions, online learning must also be able to require students to remain active during the activity so that this of course must pay attention to a student-centered learning system. The process of this approach is then used and is called the scientific approach. This type of research uses qualitative research using descriptive analysis. This research was conducted by observing and interviewing several related schools. The results of the study will explain or explain how the online learning process in science subjects with energy material and its changes through the fourth grade scientific approach at the Institute.